2020
DOI: 10.1055/s-0040-1721396
|View full text |Cite
|
Sign up to set email alerts
|

Do You Know What Your Scribe Did Last Spring? The Impact of COVID-19 on Medical Scribe Workflow

Abstract: Objective To understand the impact of the shift to virtual medicine induced by coronavirus disease 2019 (COVID-19) has had on the workflow of medical scribes. Design This is a prospective observational survey-based study. Setting This study was conducted at academic medical center in the United States. Participants Seventy-four scribes working in ambulatory practices within an academic medical center. Interventions All medical scribes received a survey assessing their wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Some practices have shifted to a virtual scribing model, where scribes document in-person or telemedicine visits from a remote location. 44 , 45 Many primary care practices, including CHCs, are furloughing staff. Reduced revenue due to drops in visit volume may also make it more difficult for practices to afford scribes in the foreseeable future.…”
Section: Discussionmentioning
confidence: 99%
“…Some practices have shifted to a virtual scribing model, where scribes document in-person or telemedicine visits from a remote location. 44 , 45 Many primary care practices, including CHCs, are furloughing staff. Reduced revenue due to drops in visit volume may also make it more difficult for practices to afford scribes in the foreseeable future.…”
Section: Discussionmentioning
confidence: 99%
“…In a quantitative study at a large academic hospital, the researchers reported that scribes have taken on some new roles due to COVID-19. Some scribes are doing pre-charting only, remote scribing for virtual visits, and remote scribing for traditional in person visits [ 35 ]. Due to redeployment, scribes are aiding in non-visit-related tasks like “working in the virtual help desk… check point staffing, and chart abstraction” [ 35 p 809 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some scribes are doing pre-charting only, remote scribing for virtual visits, and remote scribing for traditional in person visits [ 35 ]. Due to redeployment, scribes are aiding in non-visit-related tasks like “working in the virtual help desk… check point staffing, and chart abstraction” [ 35 p 809 ]. This shows that the scribes’ role could expand to include activities not typically involved in scribing duties.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations